Genetic Mosaicism and Cancer: Cause and Effect - Lichtenstein, Anatoly V. (Cancer research (Chicago, Ill.), 2018)
Increasing theoretical and experimental evidence suggests that the genomes of both normal and cancer cells are subject to continuous changes as a result of copying errors during replication, defects in chromosome segregation during mitosis, and direct chemical attacks by reactive oxygen species. The process of cellular genetic diversification begins during embryonic development and continues throughout life, leading to the phenomenon of somatic mosaicism. New information about the genetic diversity of cells composing the body makes us reconsider the existing concepts of cancer etiology and pathogenesis. Here, I suggest that a progressively deteriorating microenvironment (“soil”) generates the cancerous “seed” and favors its development. Cancer Res; 78(6); 1375–8. ©2018 AACR.